2008
DOI: 10.1128/aac.01103-07
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Imipenem-Resistant Enterobacter Species: Emergence of KPC-2 Carbapenemase, Molecular Characterization, Epidemiology, and Outcomes

Abstract: The prevalence of isolation of imipenem-resistant Enterobacter (IRE) strains is rising, with potential serious consequences in terms of patients' outcomes and general care. The study objective was to define the various epidemiological aspects of the isolation of these strains in comparison to cases of isolation of imipenemsusceptible Enterobacter (ISE) strains. Molecular analysis of IRE strains included genotyping and defining the presence of carbapenemases. We conducted a matched retrospective case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
1
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 34 publications
3
131
1
16
Order By: Relevance
“…A recent study by Marchaim et al (2008) showed that the mortality rate was significantly higher for patients infected with KPC-producing Enterobacter species (33 %, 11/33) than for those infected with imipenem-susceptible strains (6 %, 2/33) (2008). Another case-control study reported by Patel et al (2008) showed that patients associated with carbapenem-resistant K. pneumoniae (mostly KPC-producing) infection were more likely to die during hospitalization than those associated with carbapenem-susceptible K. pneumoniae infection (48 vs 20 %; Patel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Marchaim et al (2008) showed that the mortality rate was significantly higher for patients infected with KPC-producing Enterobacter species (33 %, 11/33) than for those infected with imipenem-susceptible strains (6 %, 2/33) (2008). Another case-control study reported by Patel et al (2008) showed that patients associated with carbapenem-resistant K. pneumoniae (mostly KPC-producing) infection were more likely to die during hospitalization than those associated with carbapenem-susceptible K. pneumoniae infection (48 vs 20 %; Patel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As espécies de Enterobacter estão entre os Gram-negativos mais comuns em IRAS, sendo consideradas patógenos hospitalares emergentes, que comprometem principalmente pacientes internados em Unidades de Terapia Intensiva (UTI) e imunodeprimidos (6)(7)(8)(9). Estudos demonstram que estão associados com até 8 % de casos de bacteremias hospitalares e são o segundo patógeno Gram-negativo mais comum em pneumonias em pacientes de UTI em algumas casuísticas (6)(7)(8)(9) .…”
Section: Enterobacter Spp E Infecções Relacionados a Assistência à Sunclassified
“…Estudos demonstram que estão associados com até 8 % de casos de bacteremias hospitalares e são o segundo patógeno Gram-negativo mais comum em pneumonias em pacientes de UTI em algumas casuísticas (6)(7)(8)(9) .…”
Section: Enterobacter Spp E Infecções Relacionados a Assistência à Sunclassified
See 2 more Smart Citations